Effect of Î²-amino butyric acid in induction of resistance against Xanthomonas campestris pv. campestris in cabbage - DINESH SINGH, B.T. RAGHAVENDRA* and (Indian Phytopathology, 2017)
A defense activator chemical, Î²-aminobutyric acid (BABA) is capable of inducing local as well as systemic resistance against numerous plant pathogens. An experiment was conducted to evaluate induction of defense related enzyme peroxidase (POX) by BABA for imparting systemic resistance against Xanthomonas campestris pv. campestris (Xcc) inciting black rot disease of cabbage. Effect of BABA (1000 Âµg/ml) on the induction of POX activity in the leaves of cabbage resistant cv. Pusa Mukta and susceptible cv. Golden Acre in response to BABA and X. campestris pv.campestris revealed that the POX was found increasing in BABA + Xcc treated plants and reached maximum level at 5 days after inoculation, in comparision with BABA or Xcc treated alone. The bacterial population of X. campestris pv. campestris was also reduced significantly in both the cultivars of cabbage treated with BABA (1000 Âµg/ml) as compared to control (water) treated plants. The level POX activity was observed to be low in both uninoculated and inoculated susceptible cv. Golden Acre as compared to resistant seedlings during time course. Thus explaining the importance of POX activity in reducing population level of X. campestris pv. campestris, whose activity was enhanced with the application of BABA.